2022
DOI: 10.1101/2022.02.13.480262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective mitochondrial-lysosomal axis promotes extracellular vesicles release of mitochondrial components in Huntington’s Disease

Abstract: Mitochondrial and autophagy dysfunction are mechanisms proposed to be involved in the pathogenesis of several neurodegenerative diseases. Huntington's disease (HD) is a progressive neurodegenerative disorder associated with mutant Huntingtin-induced abnormalities in neuronal mitochondrial dynamics and quality control. Former studies suggest that the removal of defective mitochondria may be compromised in HD. The mitochondrial quality control is a complex, well-orchestrated pathway that can be compromised throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 77 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…Additionally, Todkar et al proposed that to prevent the secretion of oxidised proteins and consequent activation of the immune system, cells can selectively target ROSinduced mitochondrial proteins-containing EVs to lysosomes for degradation [166]. However, our lab recently showed that an impairment in the mitochondrial-lysosomal axis can promote the release of mitochondrial DAMPs in EVs [88]. Mitochondrial components can be secreted through the endocytic pathway and later be released into the extracellular space as EVs [175].…”
Section: Mitochondrial Damps In Extracellular Vesicles As Inflammasom...mentioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, Todkar et al proposed that to prevent the secretion of oxidised proteins and consequent activation of the immune system, cells can selectively target ROSinduced mitochondrial proteins-containing EVs to lysosomes for degradation [166]. However, our lab recently showed that an impairment in the mitochondrial-lysosomal axis can promote the release of mitochondrial DAMPs in EVs [88]. Mitochondrial components can be secreted through the endocytic pathway and later be released into the extracellular space as EVs [175].…”
Section: Mitochondrial Damps In Extracellular Vesicles As Inflammasom...mentioning
confidence: 98%
“…Importantly, in most neurodegenerative disorders, the inflammation is not driven by a pathogen, suggesting that neuroinflammation might be triggered by autologous molecules. Excessive mitochondrial damage associated to impaired mitophagy, commonly observed in neurodegenerative disorders [87], can lead to the release of mtDAMPs into the cytoplasm and extracellular environment, thus enhancing the neuroinflammatory process [88]. Moreover, sustained mitochondrial dysfunction leads to cell death which is aggravated in the central nervous system (CNS) due to the high metabolic demand and the limited capacity of neuronal regeneration [80].…”
Section: Damage-associated Molecular Patterns (Damps) Released From M...mentioning
confidence: 99%
See 3 more Smart Citations